A 28-year-old man with chest and joint pains. Issue 10 (29th December 2015) - Ertel, Andrew W; Romano, Simone; Farzaneh-Far, Afshin
Abstract : Clinical introduction: A 28-year-old man with extensive travel history to developing countries was hospitalised for intermittent sharp chest pains, worst when supine and with inspiration. Two weeks prior to presentation, he had suffered a flu-like illness with a sore throat, which was resolving. Physical examination was notable for mild fever and tachycardia with cervical lymphadenopathy and painful bilateral knee and wrist effusions. Cardiac auscultation was remarkable for a soft early-peaking systolic murmur over the aortic area with a decrescendo early diastolic murmur along the left sternal edge. There was mild leucocytosis, elevation of serum troponin and acute-phase reactants with an ECG showing sinus tachycardia. Echocardiographic windows were extremely limited but suggested the presence of pericardial effusion and aortic regurgitation. Cardiac MRI was performed (figure 1). Viral, microbiological and autoimmune testing was remarkable only for significant elevation of antistreptolysin-O titres (1450 IU rising to 1940 IU, normal <200 IU). Pericardiocentesis revealed an exudative effusion, which was negative by cytology and microbiological analysis, including for tuberculosis and fungi. Question: The most appropriate next step is? Coronary angiography Endomyocardial biopsy Treatment with colchicine for 3 months Treatment with corticosteroids Treatment with high-dose salicylates and long-term penicillin For the answer see page 808 For the question see page 769